Haemodynamic response to crystalloids or colloids in shock: an exploratory subgroup analysis of a randomised controlled trial. Issue 10 (6th October 2017) - Heming, Nicholas; Elatrous, Souheil; Jaber, Samir; Dumenil, Anne Sylvie; Cousson, Joël; Forceville, Xavier; Kimmoun, Antoine; Trouillet, Jean Louis; Fichet, Jérôme; Anguel, Nadia; Darmon, Michael; Martin, Claude; et al.
Abstract : Objective: To compare the haemodynamic effect of crystalloids and colloids during acute severe hypovolaemic shock. Design: Exploratory subgroup analysis of a multicentre randomised controlled trial (Colloids Versus Crystalloids for the Resuscitation of the Critically Ill, CRISTAL, ClinicalTrials.gov NCT00318942 ). Setting: CRISTAL was conducted in intensive care units in Europe, North Africa and Canada. Participants: Current analysis included all patients who had a pulmonary artery catheter in place at randomisation. 220 patients (117 received crystalloids vs 103 colloids) underwent pulmonary artery catheterisation. Intervention: Crystalloids versus colloids for fluid resuscitation in hypovolaemic shock. Outcome measures: Haemodynamic data were collected at the time of randomisation and subsequently on days 1, 2, 3, 4, 5, 6 and 7. Results: Median cumulative volume of fluid administered during the first 7 days was higher in the crystalloids group than in the colloids group (3500 (2000–6000) vs 2500 (1000–4000) mL, p=0.01). Patients in the colloids arm exhibited a lower heart rate over time compared with those allocated to the crystalloids arm (p=0.014). There was no significant difference in Cardiac Index (p=0.053), mean blood pressure (p=0.4), arterial lactates (p=0.9) or global Sequential Organ Failure Assessment score (p=0.3) over time between arms. Conclusions: During acute severe hypovolaemic shock, patients monitored by a pulmonary artery catheter achieved broadly similar haemodynamic outcomes, using lower volumes of colloids than crystalloids. The heart rate was lower in the colloids arm.